KOMITMEN LINGKUNGAN DAN SOSIAL: APAKAH BERMANFAAT BAGI NILAI PERUSAHAAN? - Gunibala, Zakir; Maharani, Satia Nur; Pujiningsih, Sri (Jurnal Akuntansi, 2025)
This study aims to analyze the effect of ESG (Environmental, Social, and Governance) disclosure and environmental performance on firm value with board size as a moderating variable. This study uses multiple regression analysis and moderation test on data from 30 industrial and energy sector companies listed on the Indonesia Stock Exchange (IDX). The results showed that ESG disclosure and environmental performance had no significant effect on firm value. In addition, board size does not moderate the relationship between ESG disclosure and environmental performance on firm value. This study expands the understanding of the dynamics of ESG disclosure and environmental performance in relation to firm value and explores the role of board size as a moderating factor. The findings provide practical insights for corporate management, investors and policy makers in an effort to encourage more sustainable business practices.